Evaluation of Actual and Potential Land Suitability on Lime Post-Mining Land in Padalarang, West Bandung (Jurnal Pengelolaan Lingkungan Pertambangan, 2025)
Open Access Land (OAL) refers to former mining areas outside the mining business license zones, which often experience severe degradation due to illegal mining activities without reclamation. The negative impacts of mining activities on OAL must be addressed promptly through reclamation efforts. Developing a rehabilitation plan for OAL requires comprehensive data, including land suitability evaluation data. This study was conducted on former limestone mining areas in the Gunung Hawu-Pabeasan region, Padalarang, West Bandung Regency, with the objective of assessing current and potential land suitability, identifying limiting factors, and providing rehabilitation recommendations. Soil samples were collected from four distinct locations, including natural soil and OAL sites (1,2, and 3), and analyzed in the laboratory to determine soil characteristics. The analysis revealed significant differences between natural soil and OAL, particularly in terms of effective depth, soil physical and chemical properties. Land suitability evaluation based on FAO guidelines, indicated that natural soil is classified as marginally suitable (S3) for certain crops compared to OAL, with main limiting factors including nutrient retention and water availability. OAL soils are mostly classified as not suitable (N) for the studied crops, primarily due to limitations in effective soil depth and water availability. OAL requires further improvements to enhance land suitability through fertilization and proper root zone management. After rehabilitation, the potential land suitability improves but remains in S2 and S3 classes depending on the type of crop. Teak, sengon, and pine are suitable for revegetation but still require proper land management and improvement to enhance land suitability